Genetic erosion and escalating extinction risk in frogs with increasing wildfire frequency. Issue 3 (15th November 2016) - Potvin, Dominique A.; Parris, Kirsten M.; Smith Date, Katie L.; Keely, Claire C.; Bray, Rebecca D.; Hale, Joshua; Hunjan, Sumitha; Austin, Jeremy J.; Melville, Jane
Summary: Wildfires are increasing in both frequency and intensity in many ecosystems, with climate change models predicting further escalations in fire‐prone environments. Set against this background is the global decline of amphibians, with up to 40% of species facing extinction from multiple additive threats. Despite these disturbing figures, it is currently unclear how increasing fire frequency may impact the long‐term persistence of frog populations. Following a severe wildfire in south‐eastern Australia in 2009, field surveys indicated healthy tree frog populations. However, the 2009 fire had significant impacts on genetic diversity, including increased levels of inbreeding and declines in effective population size. Using stochastic population modelling under a range of fire‐frequency scenarios, we demonstrate that amphibian populations in fire‐prone environments may be increasingly vulnerable to extinction, particularly where rates of immigration are low. Synthesis and applications . This study of amphibian population genetics before and after a major wildfire emphasizes the importance of integrating both ecological and genetic data into population models. This will help managers make more appropriate conservation decisions regarding fire management of natural environments, especially those containing threatened populations. Priorities for agencies involved in planning controlled burns should consider carefully the timing of controlled burns, along with maintaining habitat connectivity. Abstract : This study of amphibian population genetics before and after a major wildfire emphasizes the importance of integrating both ecological and genetic data into population models. This will help managers make more appropriate conservation decisions regarding fire management of natural environments, especially those containing threatened populations. Priorities for agencies involved in planning controlled burns should consider carefully the timing of controlled burns, along with maintaining habitat connectivity.